1997
DOI: 10.1002/(sici)1097-4547(19970501)48:3<264::aid-jnr9>3.0.co;2-d
|View full text |Cite
|
Sign up to set email alerts
|

Replenishment of docosahexaenoic acid in n-3 fatty acid-deficient fetal rats by intraamniotic ethyl-docosahexaenoate administration

Abstract: A procedure for intraamniotic ethyl-docosahexaenoate (Et-DHA) administration was used to restore the docosahexaenoic acid (DHA; 22:6 n-3) levels in n-3-deficient fetal rats. The state of deficiency, characterized by a 34% and 60% decrease in DHA content of fetal brain and liver, respectively, was attained by feeding the pregnant dams from day 8 and up to 20 days gestation, with an n-3 linolenic acid-deprived diet. After a single intraamniotic administration of Et-DHA on day 18 or 19, a rapid increase in both f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 57 publications
2
12
0
Order By: Relevance
“…Conversely, weanlings nursed on control dams had elevated levels of n-6 DPA in both plasma and brain lipids, despite the fact that the proportion of n-6 DPA in milk FA was not significantly different between milk derived from transgenic and control dams. Many other studies with n-3-deficient diets have reported that a decrease in DHA is accompanied by an increase in n-6 DPA, and the DHA:n-6 DPA ratio can be used as an indicator of n-3 FA deficiency (24). This ratio was 0.75 for the control pups' brains, as compared with 5.39 for the brains of pups nursed on transgenic dams.…”
Section: Discussionmentioning
confidence: 84%
“…Conversely, weanlings nursed on control dams had elevated levels of n-6 DPA in both plasma and brain lipids, despite the fact that the proportion of n-6 DPA in milk FA was not significantly different between milk derived from transgenic and control dams. Many other studies with n-3-deficient diets have reported that a decrease in DHA is accompanied by an increase in n-6 DPA, and the DHA:n-6 DPA ratio can be used as an indicator of n-3 FA deficiency (24). This ratio was 0.75 for the control pups' brains, as compared with 5.39 for the brains of pups nursed on transgenic dams.…”
Section: Discussionmentioning
confidence: 84%
“…supply of lipids or FAs has not been done until very recently, when a method of DHA administration to late gestation fetal rats has been devised (Green and Yavin, 1995) by the intra-amniotic injection of Et-DHA in vivo. In rats fed both an n-3 FA-sufficient diet (Green and Yavin, 1995) or an n-3 FA-deficient diet (Green et al, 1997), fetal brain lipid DHA content increased significantly following a single intra-amniotic Et-DHA administration. In both studies, the DHA increase was steeper for the fetal liver than for the brain, suggesting that under certain conditions, the fetal liver may have an important role in the supply of DHA to the brain.…”
Section: The Fetal Gastrointestinal Route Of Brain Dha Supplymentioning
confidence: 98%
“…Animal studies have revealed direct correlations between the FA composition of the maternal diets and that of the brain and retina in the offsprings in several species (Bourre et al, 1984;Neuringer et al, 1986;Yonekubo et al, 1993). For example, feeding pregnant rats an n-3 FA-deficient diet for only the last 2 weeks of pregnancy resulted in a more than 30% decrease in fetal brain DHA and an almost 120% increase in DPA as compared to fetal brains from control, n-3 FA-sufficient diet-fed rats (Green et al, 1997). In a meticulous study in the pregnant guinea pig it was shown that a transient, mid-gestational increase in maternal liver concentration of 16:0/22:6 PC precedes the progressive increase in total PC concentration toward term (Burdge and Postle, 1994).…”
Section: Maternal Dha Supplymentioning
confidence: 99%
“…For these studies we used rats fed an n-3 FA sufficient or deficient diet. The state of deficiency, characterized by a 34% and 60% decrease in DHA content of fetal brain and liver, respectively, was attained by feeding pregnant rats from day 8 and up to 20 days gestation, with a n-3 LoA-deprived diet (Green et al, 1997). After a single intraamniotic administration of Et-DHA on day 18 or 19, a rapid increase in both fetal brain and liver DHA was achieved.…”
Section: The Intraamniotic Route For Brain Dha Enrichmentmentioning
confidence: 99%